Spatial and temporal analysis of native vegetation coverage for compliance with the New Forest Act - Tavares, Paulo André (2021)
Compensation is one of the forms of compliance provided by Brazilian legislation as a mechanism to offset environmental impacts, which allows landowners of rural properties that do not meet their Legal Reserve requirements on their property, to compensate in third-party properties with surplus native vegetation. Failure to meet liabilities will result in the owner being punished with administrative sanctions. However, the current Forest Act (Federal Law 12.651 / 2012), provides in its article 68 that the rural owners and possessors who carried out native vegetation suppression before July 22, 2008, are obliged to fulfill the liability in accordance with the legislation in force at the time, without administrative sanctions. The complexity of the interpretation of the article due, for example, to the different concepts about phytophysiognomies contained in previous laws, in addition to the difficulty of proving historical suppression data in relation to the framework established by law, can slow down the coverage of the analysis of the deficit of native vegetation of rural properties and, consequently, the signature of a Term of Commitment by the owner in order to comply with the Environmental Regularization Program (PRA), thus increasing transaction costs in law enforcement and generating insecurity regarding validity of the chopped documents. This project aims to analyze the interpretation of the rules for the demarcation of conserved areas in rural properties in the legislation prior to current Forest Act, to generate maps of native vegetation in past data based on this interpretation, as well as maps of deficit and surplus of native vegetation to compensate for Legal Reserve, providing the government with tools for the effective implementation of PRA in the State of São Paulo.